2003
DOI: 10.1002/ejoc.200200422
|View full text |Cite
|
Sign up to set email alerts
|

To What Extent Can Nine‐Membered Monocycles Be Aromatic?

Abstract: Ab initio and density functional computations have been used to characterize the heteronins. New targets for synthesis are suggested on the basis of the results. The aromaticity of the heteronins was evaluated via numerous criteria such as magnetic properties (NICS and δH), geometric indices (Bird, BDSHRT and HOMA), aromatic stabilization energies (ASE), and the barriers to planarity. Along with the experimentally characterized cyclononatetraenyl (1CH−) and azonide (1N−) anions, the phosphonide ion (1P−, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Cyclopentadienes have long been studied as diene partners in Diels–Alder reactions. Studies by Schleyer et al showed that substituents on the C-5 position affect the electronic properties of the cyclopentadiene π-system via hyperconjugation. σ-acceptors, and in particular fluorine atoms, induce negative hyperconjugation resulting in a pseudo 4π-electron antiaromatic system (Figure a). , Some of this antiaromatic destabilization is offset by distortion of the C-X bond away from the plane of the diene (Figure b). , In contrast, electron-donating groups (i.e., silyl-substituents) favor an aromatic character of the diene. The degree of (anti)­aromaticity of cyclopentadienes directly affects the distortion energy in the cycloaddition transition state and therefore the rate of the reaction …”
Section: Inverse-electron Demand Diels-alder Cycloaddition Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclopentadienes have long been studied as diene partners in Diels–Alder reactions. Studies by Schleyer et al showed that substituents on the C-5 position affect the electronic properties of the cyclopentadiene π-system via hyperconjugation. σ-acceptors, and in particular fluorine atoms, induce negative hyperconjugation resulting in a pseudo 4π-electron antiaromatic system (Figure a). , Some of this antiaromatic destabilization is offset by distortion of the C-X bond away from the plane of the diene (Figure b). , In contrast, electron-donating groups (i.e., silyl-substituents) favor an aromatic character of the diene. The degree of (anti)­aromaticity of cyclopentadienes directly affects the distortion energy in the cycloaddition transition state and therefore the rate of the reaction …”
Section: Inverse-electron Demand Diels-alder Cycloaddition Reactionsmentioning
confidence: 99%
“…Most 4 H- pyrazoles require heating or acid catalysis to react with strained alkenes or alkynes. However, strategically positioning σ-accepting groups (e.g., -F) at the C-4 position allow such reactions to proceed at room temperature by inducing hyperconjugative antiaromaticity (Figure a). , Recently, 4,4-difluoropyrazoles (DFP) were proposed as dienes suitable for use in bioorthogonal IEDDA reactions. , The electrophilic geminal fluorine groups invoke hyperconjugative antiaromaticity which destabilizes the ground state and reduces the energy required to distort the diene in the transition state of the reaction with dienophiles. BCN reacted faster with diphenyl-DFP ( k 2 = 5.2 M –1 s –1 ) than with 3,6-diphenyltetrazine ( k 2 = 3.2 M –1 s –1 ) .…”
Section: Inverse-electron Demand Diels-alder Cycloaddition Reactionsmentioning
confidence: 99%